Smart Phone, Smart Science: How the Use of Smartphones Can Revolutionize Research in Cognitive Science - Dufau, Stephane; Duñabeitia, Jon Andoni; Moret-Tatay, Carmen; McGonigal, Aileen; Peeters, David; Alario, F.-Xavier; Balota, David A.; Brysbaert, Marc; Carreiras, Manuel; Ferrand, Ludovic; Ktori, Maria; Perea, Manuel; et al. (PloS one, 2011)
Investigating human cognitive faculties such as language, attention, and memory most often relies on testing small and homogeneous groups of volunteers coming to research facilities where they are asked to participate in behavioral experiments. We show that this limitation and sampling bias can be overcome by using smartphone technology to collect data in cognitive science experiments from thousands of subjects from all over the world. This mass coordinated use of smartphones creates a novel and powerful scientific "instrument" that yields the data necessary to test universal theories of cognition. This increase in power represents a potential revolution in cognitive science.